MONOCYTIC MYELOID-DERIVED SUPPRESSOR CELL EXPANSION AFTER CARDIAC SURGERY WITH CARDIOPULMONARY BYPASS INDUCES LYMPHOCYTE DYSFUNCTION. Issue 6 (21st December 2022) - Lesouhaitier, Mathieu; Uhel, Fabrice; Gregoire, Murielle; Gacouin, Arnaud; Frerou, Aurélien; Gaudriot, Baptiste; Bendavid, Claude; Boukthir, Sarrah; Le Tulzo, Yves; Verhoye, Jean-Philippe; Flecher, Erwan; Roussel, Mikael; et al.
ABSTRACT: Cardiac surgery with cardiopulmonary bypass (CPB) is associated with an immune paresis that predisposes to the development of postoperative infections and sepsis. Among factors responsible for CPB-induced immunosuppression, circulating myeloid-derived suppressor cells (MDSCs) have been found to induce early lymphocyte apoptosis and lymphocyte proliferation inhibition. However, the mechanisms involved are not fully understood. In this study, we found that the main lymphocyte subsets decreased significantly 24 h after cardiac surgery with CBP. As expected, cardiac surgery with CPB induced a monocytic MDSC expansion associated with an increased T-cell apoptosis and decreased proliferation capacity. Noteworthy, granulocytic MDSCs remain stable. Myeloid-derived suppressor cell depletion restored the ability of T-cell to proliferate ex vivo . After CPB, indoleamine 2, 3-dioxygenase activity and IL-10 plasma level were increased such as programmed death-ligand 1 monocytic expression, whereas plasma level of arginine significantly decreased. Neither the inhibition of indoleamine 2, 3-dioxygenase activity nor the use of anti–programmed death-ligand 1 or anti–IL-10 blocking antibody restored the ability of T-cell to proliferate ex vivo . Only arginine supplementation restored partially the ability of T-cell to proliferate.